Features of Moral and Patriotic Education of Preschoolers in the Context of the Modern Educational Environment - Tronko, Svitlana (Journal of Education Culture and Society, 2025)
Aim. The study focuses on the impact of interactions between educators and parents on the development of patriotic values and feelings in older preschool children (5–6 years old) as a crucial component of personality development. To demonstrate the effectiveness of moral and patriotic education in preschoolers under modern educational conditions.Methods. The research employed diagnostic interviews, experimental situations, and behavioural task analysis to evaluate the cognitive, emotional, and behavioural components of patriotic qualities.Results. The proposed pedagogical methods proved effective: the proportion of children with a high level of patriotic qualities in the experimental group significantly increased compared to the control group. The effectiveness of the methods was statistically confirmed: the Student's t-test indicated significant differences between the experimental and control groups. Specifically, the average level of patriotic qualities in the experimental group increased by 35%, while the low level decreased to a minimum (5%).Conclusion. These results confirm the productivity of the proposed methodology, which integrates traditional and innovative approaches to education.Originality. The study reveals the integration of traditional and modern educational methods through the use of surveys, observations, and group work with children. The improvement of educational programmes for preschools and the development of a practical programme for working with older preschoolers aimed at fostering moral and patriotic qualities.Cognitive value. The study has cognitive value, as it reveals the peculiarities of integrating traditional and modern methods of education in working with preschool children. The use of questionnaires, observation, and group forms of work made it possible to outline effective approaches to the formation of moral and patriotic qualities in older preschoolers. Along with this, the study has certain limitations related to the sample (limited in terms of territory or quantity), as well as the specificity of the applied methods, which require further scientific research and approval of the developed program in a broader educational context.